Comparison of the Outcome between Conventional Open Technique and Minimally Invasive Technique Using Dynamic Hip Screw for Fixation of Inter-Trochanteric Fracture of Femur - Maharjan, Rajiv; Paneru, S.R.; Rijal, R.; Chaudhary, P.; Khanal, G.P. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Inter-trochanteric fracture of femur causes significant morbidity and mortality in elderly. Dynamic Hip Screw (DHS) fixation is the most effective and safe method of treatment. Conventional open technique (CDHS) is the popular and familiar one; however, minimal incision technique (MIDHS) has many advantages like: smaller incision, lesser dissection/blood loss, less requirement of transfusion, less painful, faster recovery etc. Objectives: To Compare CDHS and MIDHS technique of DHS fixation for inter-trochanteric fracture femur in terms of functional outcome, safety and associated complications (if any). Methods: Eligible patients presenting within study period were randomized into CDHS group (n= 33) and MIDHS group (n= 32). Success of randomization was tested by analyzing demographics, injury characteristics and pre-op. clinical data (p> 0.05). They were followed up at 2, 6, 12, 24 and 52 weeks post-op. for clinico-radiological and functional assessment. Results: The duration of surgery, lag screw positioning, post-operative hospital stay and surgical site infection were not significantly different between the groups. However, need for blood transfusion, length of incision and post-operative VAS score for pain were significantly lesser for MIDHS group than CDHS group (p< 0.05). Patients in MIDHS group started walking with aids significantly earlier in post-operative recovery period. The Harris Hip Score at final follow-up and grading of the results and surgical complications were not significantly different between the groups. Conclusion: The minimal incision technique had various immediate / short term advantages over conventional technique; like: minimal scar, minimal soft tissue dissection / less blood loss requiring less transfusion, lesser pain in post-operative period and ability to ambulate early.